Technological Methodological Basis for Developing Creative Activities of Students in A Distance Learning Environment - Xoshimova Feruzaxon Baxodirovna (Web of Journals Publishing, 2023)
In the vocational education environment, there are suggestions on the development of creativity and technological methodologies for improving students' creativity. In the vocational education environment, the emphasis is also placed on the significant components of the development of creative activities of the students.
Keywords: Vocational education, creativity, ability, pedagogical foundations, methodological foundations, environment.